RANCANG BANGUN SISTEM INFORMASI E-PROCUREMENT PADA PDAM SURYA SEMBADA KOTA SURABAYA - Haryanto, Hedy; Arifin, Moch.; Sutanto, Teguh (Jurnal Sistem Informasi dan Komputerisasi Akuntansi (JSIKA), 2013)
In a goverment instation, the procurement of goods and services is a very important activity. The problem faced in this era is the procurement of goods or services process done manually. Refers to the procedure which must done to do the Keputusan Presiden No. 54 Tahun 2010 (Presidential Decree No. 54, 2010), its process will take much time and cost. The solution to handle the problem is by making an e-procurement application which help the procurement of goods or services. With e-procurement then some supplying process steps can be done by internet, there are the announcement of the project was auctioned, registration of candidate partner, the tender document, arranging partner list, announcement of winners, and so on. Depends on the implementation result and testing which done by researcher with qualification method so the e-procurement can help the solution of procurement of goods or services that is as long as this is done manually. Keyword: knowledge, multimedia, video, Knowledge Management System.